Phytosociological study of the forest vegetation of Kyiv urban area (Ukraine) - Goncharenko, Igor; Yatsenko, Halyna (Hacquetia, 2020)
The current study presents the floristic-sociological classification of the forest vegetation of the Kyiv urban area. We identified 21 associations and variants belonging to 7 classes, 8 orders and 10 alliances of the forest vegetation. Some of them were described with new names, particularly, in the classes of Alno glutinosae-Populetea albae (Aristolochio clematitis-Populetum nigrae ass. nov. hoc loco), Robinietea (Galio aparines-Aceretum negundi ass. nov. hoc loco), Galio-Urticetea (Lapsano communis-Urticetum dioicae ass. nov. hoc loco), Quercetea robori-petraeae (Poo nemoralis-Quercetum roboris ass. nov. hoc loco), Vaccinio-Piceetea (Luzulo pilosae-Pinetum sylvestris ass. nov. hoc loco, Calamagrostio epigeii-Pinetum sylvestris ass. nov. hoc loco). Vegetation classification was conducted using the original DRSA algorithm (Distance-Ranked Sorting Algorithm) based on the k-nearest neighbors clustering approach. The phytocoenons were analyzed using ordination, phytoindication, and by inter-cluster similarity evaluation and described by traits of synmorphology, ecological specificity, distribution data, phytosociological spectrum, and syntaxonomical relations.